Effect of Training and Work Environment on Employee Performance at PT Marindo Makmur Usahajaya Sidoarjo - Annisa Dwi Permatasari; Bayu Airlangga Putra; Elok Damayanti (NAROTAMA UNIVERSITY, Indonesia, 2020)
This study discusses how the influence of training and work environment on employee performance at PT Marindo Makmur Usahajaya Sidoarjo. This study aims to determine the effect of training, work environment on employee performance. The sampling technique in this study used the Non Probability Sampling method. Respondents in this study were 83 employees. Methods of data analysis using multiple linear regression test, with SPSS v.18 software as an analysis tool. The results of this study indicate that training variables and work environment variables partially and simultaneously have an effect on employee performance.